A Novel Topical 2% Povidone–Iodine Solution for the Treatment of Common Warts: A Randomized, Double-Blind, Vehicle-Controlled Trial. Issue 4 (December 2015) - Capriotti, Kara; Stewart, Kevin; Pelletier, Jesse; Capriotti, Joseph
Abstract Introduction Verruca vulgaris, also known as common warts, are benign skin growths caused by infection of the skin by human papillomavirus. Warts are common in both childhood and adulthood and are spread by direct contact or autoinoculation. Treatment options vary from locally destructive methods to immuno-modulatory therapy. Common warts are often resistant to treatment. Though many remedies exist, there is no consensus therapy backed by randomized-controlled clinical trials that are FDA approved for the treatment of verruca vulgaris. We describe here the results of a small, randomized, double-blind, vehicle-controlled Phase II clinical trial with a novel topical agent for the treatment of common warts. Methods Twenty-one patients aged 8 years and older were enrolled in this single-center, randomized, double-blind, vehicle-controlled Phase II clinical trial to assess the efficacy, safety and tolerability of twice-daily application of a novel 2% topical povidone–iodine solution in a dimethyl sulfoxide vehicle for 12 weeks duration. Patients were block randomized into two groups consisting of 14 patients in the active arm and 7 patients in the vehicle only arm. All patients were evaluated at baseline, week 4, 8 and 12 and the results compared for overall Global Aesthetic Improvement Scale (GAIS) improvement. Results There were a total of 21 patients included in the study. Sustained improvement in the GAIS scale was observed at the final week 12 exam visit in 77% of subjects in the treatment arm and 33% of patients in the control arm. There were no serious safety or tolerability issues reported. Conclusion Twice-daily topical povidone–iodine solution in the novel vehicle employed for this study is an effective, safe and easy-to-use treatment for common warts. Further study of this agent in expanded Phase II and Phase III clinical trials is warranted. Funding ALC Therapeutics LLC.